Structural intensity analysis of a large container carrier under harmonic excitations of propulsion system - Dae-Seung Cho; Kyung-Soo Kim; Byung-Hwa Kim (International Journal of Naval Architecture and Ocean Engineering, 2010)
The structural intensity analysis, which calculates the magnitude and direction of vibrational energy flow from vibratory velocity and internal force at any point of a structure, can give information on dominant transmission paths, positions of sources and sinks of vibration energy. This paper presents a numerical simulation system for structural intensity analysis and visualization to apply for ship structures based on the finite element method. The system consists of a general purpose finite element analysis program MSC/Nastran, its pre- and post-processors and an in-house program module to calculate structural intensity using the model data and its forced vibration analysis results. Using the system, the structural intensity analysis for a 4,100 TEU container carrier is carried out to visualize structural intensity fields on the global ship structure and to investigate dominant energy flow paths from harmonic excitation sources to superstructure at resonant hull girder and superstructure modes.